Starch–maleate–polyvinyl alcohol hydrogels with controllable swelling behaviors - Pang, Suh Cem; Chin, Suk Fun; Tay, Soon Hiang; Tchong, Fui Mui (Elsevier, 2011)
Starch–maleate–polyvinyl alcohol (SMP) hydrogels were prepared by reacting polyvinyl alcohol (PVA) with maleic acid (MA) substituted sago starch (SS). The substitution of MA and PVA onto the polysaccharide chain of sago starch was evidenced by the FTIR spectra which showed the presence of the carbonyl group absorption band of maleate ester, and increased intensity of the C–H stretching absorption band. The surface morphology of SMP hydrogels as revealed by SEM micrograph was membrane-like with continuous matrices, and these samples were insoluble in both water and alkaline aqueous solution. TGA analysis showed that the SMP hydrogel exhibited higher thermal stability as compared to the RS, RPVA and SM samples. SMP hydrogel regenerated by freeze-drying showed substantially higher swelling ratio than hydrogel regenerated by direct precipitation under controlled conditions. The swelling behavior of SMP hydrogel could be easily controlled and modulated by varying the feeding composition of precursors or the regeneration methods. The high potential utility of SMP hydrogels in biomedical applications is envisaged by its biocompatibility, low toxicity, ease of preparation and low cost.